DIFFERENCES IN METABOLOMICS IN CHILDREN WITH HIGH AND LOW ARTERIAL STIFFNESS. A CASE-CONTROL STUDY. (June 2022) - Poikilidou, Maria; Yavropoulou, Maria; Tsave, Olga; Stamou, Maria; Grammatikopoulou, Artemida; Georgianos, Panagiotis; Zebekakis, Pantelis
Abstract : Objective: Studies in children have shown a progressive increase in arterial stiffness by measuring pulse wave velocity (PWV) during childhood, indicating a structural alteration to the arterial wall starting already in early life. Metabolomic studies also show differences in molecules between different disease states in children. The aim of the current study was to identify molecular markers between age and gender-matched children with high and low PWV. Design and method: The study included the screening of 132 children that came for random visits to a tertiary pediatric clinic. 50 children (25 in the highest PWV tertile-Group 1, and 25 in the lowest PWV tertile-Group 2) were chosen for the metabolomic study. The groups were matched for age and gender and underwent an ABPM, and PWV, Aix measurements as well as measurements of central BP. We used t-test to explore differences between the two groups. We used mass spectrometry and constructed a heat map displaying the differences in each metabolite concentration between the two groups. Results: The mean age of the study population was 11.4 ± 2.7 years. Group 1 had significantly higher BMI percentiles than Group 2 (94.7 ± 8.7 and 74.3 ± 27.6, p < 0.001), higher 24-hour SBP (117.3 ± 110.9 ± 9.0mmHg, p = 0.025) and higher 24-hour DBP (70.7 ± 7.3 vs 65.8 ± 5.8mmHg, p = 0.018), higher central SBP (95.1 ± 8.5 vs 89.3 ± 9.7mmHg, p = 0.028), and DBP 69.6 ± 8.6 vs 60.8 ± 11.0mmHg, p = 0.003). Similarly, significant differences occurred also between clinic SBP and DBP. Table 1. shows the metabolites that were significantly upregulated in Group 1. Conclusions: The current metabolomic study found differences in certain metabolites between children in the highest and lowest ends of arterial stiffness. These metabolites involve sphingolipids, sterol lipids, fatty acyls, carboxylic acids, glycerophospholipids as well as other compounds that are not yet fully identified on their properties.